On Local Convergence Analysis of Inexact Newton Method for Singular Systems of Equations under Majorant Condition - Fangqin Zhou (The Scientific World Journal)
We present a local convergence analysis of inexact Newton method for solving singular systems of equations. Under the hypothesis that the derivative of the function associated with the singular systems satisfies a majorant condition, we obtain that the method is well defined and converges. Our analysis provides a clear relationship between the majorant function and the function associated with the singular systems. It also allows us to obtain an estimate of convergence ball for inexact Newton method and some important special cases.